Terapeutyczny wymiar wywiadu socjologicznego: praktyka badawcza w kontekście wyzwań etycznych - Łuczaj, Kamil (Studia socjologiczne, 2024)
The article discusses the problems of conducting qualitative interviews in the context of their therapeutic potential and the need to prepare the research team for the fieldwork. Based on research with upwardly mobile academics (2020-2022) and a project on the biographical experience of post-transformation (2022-), in this article, I pose and answer three questions. Why do biographical interviews have the potential to morph into a therapeutic conversation? How can one prepare to conduct one? Who should give permission or recommendations for conducting such an interview? Due to the subject-matter of both projects, the interviews transformed from a typically sociological form of measuring social reality into a therapeutic or quasi-therapeutic dialogue, which met the emotional needs of the interviewees and enabled them to change their behavior (e.g., through increased self-reflexivity).